(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article examines the theme of love in the works of Chingiz Aitmatov as a spiritual and moral phenomenon. The author analyzes the following forms of love in the writer’s works: • a means of moral development; • a means of self-knowledge and spiritual poverty; • a way to overcome abstract loneliness; • the connection between tradition and personal freedom.